Free PSA is a Better Tumor Marker than Serum Total PSA in Diagnosis of Prostatic Carcinoma - Asafudullah, SM; Salam, MA; Badruddoza, SM; Rahman, M Khalilur (TAJ: Journal of Teachers Association, 2010)
Estimation of serum prostate specific antigen (PSA) has been considered as valuable non-invasive biochemical diagnostic tool for early detection of prostatic carcinoma. This cross sectional purposive study was carried out to compare the performance of serum total PSA and free PSA in terms of their sensitivity, specificity and overall diagnostic accuracy for prostatic carcinoma among clinically suspected cases. This study included a total of fifty (50) DRE (digital rectal examination) positive patients admitted in Rajshahi Medical College Hospital (RMCH) and Private hospitals in Rajshahi city during the period of January, 2006 to January, 2008. Estimation of serum total PSA and free PSA were done by ELISA (Enzyme linked immunosorbent assay) method using commercially available kits and histopathological examination of the surgically resected prostatic tissue was done for laboratory confirmation of the diagnosis of prostatic carcinoma for all patients. Diagnostic sensitivities, specificities and overall accuracy of serum total PSA and free PSA were calculated using standard formulae against histopathological diagnosis. Prostatic carcinoma was detected by histopathological examination in 41 cases out of 50 patients with the mean age of 71.2 ± 10.1 years. The sensitivity, specificity and overall diagnostic accuracy of serum total PSA (at cut off value of ≥10 ng/ml) were found to be 80.48%, 88.90% and 82.00% respectively while they were 92.68%, 77.80% and 90.00% respectively for serum percent free PSA (at cut off value of ≤25%). It is inferred that percent free PSA is a better tumor marker than serum total PSA in the diagnosis of prostate carcinoma. DOI: 10.3329/taj.v22i1.5017 TAJ 2009; 22(1): 30-35